(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Dadru is categorized under both Kshudrakusta and Mahakusta, which is a Tridoshshajavyadhi primarily vitiated by the Pitta-kapha dosha and characterized by Kandu, Raga, Pidaka, Mandala and Rukshata. It can be correlated to dermatophytosis on the basis of symptomatology and pathogenesis. As India being a tropical country, there has been a rise in chronic and relapsing dermatophytosis, with a prevalence of 65.3% and 34.6%, respectively. The study was undertaken with an intention to evaluate the combined effectiveness of Tila bakuchichurna internally and Nimbadilepa externally in the management of Dadru. The ingredients of the intervention possess Tikta rasa, Ushnnaveerya, Tridoshaghna, Krimighna, Kandughna and Kushtaghna properties in contrast to the properties of Dadru. Objectives: To clinically evaluate the combined effectiveness of Tila bakuchichurna and Nimbadilepa in the management of Dadru (dermatophytosis). Methodology: Among 34 registered participants, 30 of them completed the course of treatment. They were administered with 6gm of Tila bakuchichurna internally, once daily in the morning, before food, with Anupana of warm water and Nimbadilepa application externally, once daily in the daytime with water for a period of 30 days. Ordinal data was analysed with Friedman’s test followed by Wilcoxon signed rank test after applying Bonferroni correction with a 95% confidence interval; p<0.05 was considered significant. Results: Statistically significant improvement was observed on the parameters Kandu, Raga, Pidaka, Mandala, Rookshata, 5-D Pruritus scale and DLQI scale. Conclusion: Tilabakuchichurna and Nimbadilepa were found to be effective in the management of Dadrukusht.